Methodological orientations, academic citations, and scientific collaboration in applied linguistics: What do research synthesis and bibliometrics indicate?. (August 2021) - Amini Farsani, Mohammad; Jamali, Hamid R.; Beikmohammadi, Maryam; Ghorbani, Babak Daneshvar; Soleimani, Ladan
Abstract: Addressing meta-research is contemporaneous with a nascent call in the field of applied linguistics and L2 studies for methodological awareness. Adhering to synthetic techniques and bibliometric analysis, we manually examined and coded the methodological orientations and scientific collaboration of 3992 applied linguistics articles published in 18 leading journals from 2009 to 2018 and analyzed their citation impact. The results showed that 178 (4.5%) of articles were non-empirical and the rest were empirical. Among empirical articles, the most prevalent research approach was quantitative (42.6%), followed by mixed-methods research studies (25.9%) and qualitative studies (24.9%). Systematic reviews (2.2%) were the smallest groups. Systematic reviews had a bigger citation impact than the other three research approaches. However, there was no statistically significant difference between the number of citations of the other three approaches (i.e., quantitative, qualitative, and mixed methods). The rates of collaboration in general and international collaboration and interdisciplinary collaboration in particular were significantly higher in quantitative articles than the articles of other research approaches. Education and psychology were two disciplines that had the highest rate of collaboration with applied linguistics researchers.